Estimating concentration of fluoride in edible leaves locally grown around Raipur, Chhattisgarh - Anubhuti Jain; Ashok Kumar Mohapatra; G Y Yunus; Ram Tiwari; Abhinav Parakh; Swati Verma (Wolters Kluwer Medknow Publications, 2017)
Introduction: Fluorine is the 13th most abundant element in the earth crust and is available in various environmental, clinical, and food samples in varied concentrations. Aim: To estimate concentration of fluoride in five medicinal and five nonmedicinal edible leaves locally grown around Raipur, Chhattisgarh, India. Materials and Methods: Samples of ten medicinal and nonmedicinal edible leaves, namely, spinach (Spinacia oleracea), coriander leaves (Coriandrum sativum), chawli bhaji (Amaranthus spinach), lal bhaji (Alternanthera bettzickiana), mooli bhaji (Raphanus sativus), neem (Azadirachta indica), tulsi (Ocimum tenuiflorum), mint leaves (Mentha longifolia), betel leaves (Piper betle), and bael leaves (Aegle marmelos) were collected in the clean polyethene bags. After thorough washing with water, leaves were left to dry in ambient temperature and crushed into powder using a mixer grinder. One gram of each of the powdered samples was taken and analyzed for fluoride concentration using a 2-(4-sulfophenylazo) 1,8-dihydroxy-3,6-naphthalenedisulfonic acid trisodium salt spectrophotometric method. Results: The presence of fluoride in varied concentrations in locally grown edible leaves were analyzed. The highest concentration of fluoride was reported in tulsi (6.0 μg/g) and lowest in mint leaves (1.1 μg/g). Two edible leaves, neem and bael, showed fluoride concentration below detection limit. Conclusion: Knowledge regarding the importance of edible leaves may be lost in the near future unless efforts are made to educate younger generations about their importance. Hence, the time has come to make good use of centuries-old knowledge through modern approaches for their better economic and therapeutic utilization.